Pengembangan E-book Berbasis Problem Based Learning pada Materi Perubahan Lingkungan dan Daur Ulang Limbah untuk Siswa di MAN Karangasem - Sabrina Intan Maulida; Putu Budi Adnyana; Ida Ayu Purnama Bestari (Undiksha, 2022)
This research aims to find out the design, validity, and practicality of e-books based on problem-based learning as a teaching material for environmental change and waste recycling for grade X at MAN Karangasem. This type of research is research & development (R&D) using a 4-D development model which is modified into three stages, namely define, design, and develop. After the e-book was developed, then an assessment was carried out with validity tests by material experts and media experts and practicality tests by testing 3 students in grade X IPA 3 in an individual test, and 9 students from grade X IPA 3 in a small group test. The location of this research is at MAN Karangasem. The data obtained will be analyzed descriptively to determine the validity and practicality of PBL-based e-books. The results of this study indicate, (1) e-books based on PBL are designed in an attractive manner where the content of the material is adapted to PBL syntax, consisting of 3 sub-chapters, in each sub-chapter there are several interactive features and in accordance with the PBL syntax. PBL such as Bio-Earth News, Bio Let's Thinking, Bio MiniLab&Activyty, Bio Anova, Bio Best Info and Bio Funzone, (2) the validity of e-books based on PBL is 91.9% which is included in the very feasible criteria, and (3) the practicality of e-books based on PBL of 90.5% are included in the very practical criteria. From the results of this study, it was concluded that the e-books based on PBL that was developed was very feasible and very practical as a teaching material on environmental change and waste recycling materials for grade X at MAN Karangasem.